2014
DOI: 10.1155/2014/583039
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Vitamin D Levels in Italian Children and Adolescents: A Longitudinal Evaluation of Cholecalciferol Supplementation versus the Improvement of Factors Influencing 25(OH)D Status

Abstract: Objective. This paper aims to assess 25(OH)D levels in Italian children and adolescents identifying risk factors for 25(OH)D deficiency and to evaluate whether a normal 25(OH)D value can be restored in 25(OH)D-deficient patients. Methods. We evaluated 25(OH)D levels in 679 Italian children and adolescents (≤10, 11–20, 21–30, and >30 ng/mL were defined as severe deficiency, deficiency, insufficiency, and sufficiency, resp.). Of these, 365 25(OH)D-deficient were followed up for 1 year; 205 were treated with chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 49 publications
3
30
0
Order By: Relevance
“…The prevalence of 25(OH)D deficiency varies between 30% and 93% in different studies in adults [ 16 ], even if in Norway and Sweden the prevalence is rather low [ 17 ]. However, in a small Italian study [ 18 ], more than 80% of children showed insufficiency or deficiency of 25(OH)D; the data were confirmed in other, larger studies providing cross-sectional [ 19 ] and longitudinal data [ 20 ].…”
Section: Introductionmentioning
confidence: 68%
“…The prevalence of 25(OH)D deficiency varies between 30% and 93% in different studies in adults [ 16 ], even if in Norway and Sweden the prevalence is rather low [ 17 ]. However, in a small Italian study [ 18 ], more than 80% of children showed insufficiency or deficiency of 25(OH)D; the data were confirmed in other, larger studies providing cross-sectional [ 19 ] and longitudinal data [ 20 ].…”
Section: Introductionmentioning
confidence: 68%
“…9,10 Having said that, studies in other countries have also shown hypovitaminosis D in non tubercular or controls patients. Studies by Gray et al (Australia) (55.9%), 3 Venturini et al (Italy and United kingdom) (47%), 4 Chung et al (Korea) (97%), 11 Stagi et al (Italy) (88.7%) 12 in pediatric groups have revealed widespread low vitamin D levels. These findings raise concerns over significance and precise standards of adequate vitamin D levels in children.…”
Section: Discussionmentioning
confidence: 97%
“…In Italy in the first year of life, an intake of 400 IU/day from six to twelve months is recommended [ 12 ], even though, as reported in Table 1 , different international health organizations give specific and sometimes slightly different recommendations due to different sun exposures and study results. In children and adolescents from 1 to 18 years of age, the recommended daily intake of Vitamin D is 600 IU/day, according to the American Academy of Pediatrics [ 30 ]. However, once again, looking at Table 2 , different international health organizations give different suggestions for the 1–18 age range.…”
Section: Discussionmentioning
confidence: 99%
“…Important factors in children over one year of age are therefore sun exposure and the presence of certain risk factors for vitamin D deficiency such as non-Caucasian ethnicity, renal or liver failure, intestinal malabsorption, chronic treatment with anticonvulsants, corticosteroids, ketoconazole, antiviral and obesity. The level of recommended daily intake of vitamin D according to the American Academy of Pediatric and Italian LARN for Children between 1 and 18 years is 600 IU/day [ 30 ]. The Endocrine Society recommends for children at risk of deficiency an intake of 600 IU/day–1000 IU/day.…”
Section: Vitamin D In the Childhoodmentioning
confidence: 99%